Sufisme Ki Hajar Dewantara - Wahyudi, Chafid (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2015)
This article explores how Ki Hajar Dewantara has built his world of reality formulation. He has a sufism epistemology in establishing of his thinking. His sufism epistemology built evidently buried by well-established theories stating that Islam in Indonesia is a syncretic Islam, then labeled as religion Kejawen initiated as a religion abangan. But others say that the history of Islam in Java is not Islam Kejawen. On the contrary, it is Islam that affiliated with Sufism. This fact becomes important when the author had to review epistemology of Ki Hajar Dewantara. Because the reality is open to the fact that his epistemology is Sufism epistemology that puts knowledge about the duality of unity. Based on the epistemology, he give a clear interpretation of the relationship between man and nature that leads to the divine reality. Theoretically God created the universe as evidence or sign of existence and people should know about it. Armed with the epistemology, Manunggaling Kawula Gusti term can be interpreted in two ways, first it means that humans have the values of divinity, second, it means united with nature.